2022
DOI: 10.1002/ocea.5328
|View full text |Cite
|
Sign up to set email alerts
|

France and Oceanian Sovereignties

Abstract: The character of sovereignty in its constitution, expression, and experience across Pacific Islands has come into renewed focus over recent years. Decades after the onset of the post‐war period of decolonization and independence, non‐self governing French territories in Oceania are seeing communities chart and navigate new relationships with sovereignty conceptions and practices across local, regional, and global scales. These navigations often evidence striking articulations of authority, rights, governance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Contemporary research has shown that MSP often applies interdisciplinary approaches and practices to the use of available resources, extracting knowledge and information from oral traditions and local cultural values of indigenous peoples [85][86][87][88][89][90][91]. These practices are linked to mechanisms such as flexible user rights and land tenure, adaptations for the generation, accumulation and transmission of ecological knowledge, institutional dynamics, mechanisms for cultural internalization of traditional practices and associated worldviews and cultural values that contribute to both increased community solidarity, community engagement and voluntary compliance, providing proper 'rules' for marine and coastal ecosystem management [92,93]. Lavoie et al mention indigenous women's substantial contribution to preserving cultural values and the crossgenerational transfer of traditional knowledge and practices linked with the exploitation of natural resources [94].…”
Section: Light Blue -"Cultural Values Indigenous Traditional Knowledg...mentioning
confidence: 99%
“…Contemporary research has shown that MSP often applies interdisciplinary approaches and practices to the use of available resources, extracting knowledge and information from oral traditions and local cultural values of indigenous peoples [85][86][87][88][89][90][91]. These practices are linked to mechanisms such as flexible user rights and land tenure, adaptations for the generation, accumulation and transmission of ecological knowledge, institutional dynamics, mechanisms for cultural internalization of traditional practices and associated worldviews and cultural values that contribute to both increased community solidarity, community engagement and voluntary compliance, providing proper 'rules' for marine and coastal ecosystem management [92,93]. Lavoie et al mention indigenous women's substantial contribution to preserving cultural values and the crossgenerational transfer of traditional knowledge and practices linked with the exploitation of natural resources [94].…”
Section: Light Blue -"Cultural Values Indigenous Traditional Knowledg...mentioning
confidence: 99%
“…Contemporary research shows that coastal and marine management often applies interdisciplinary approaches and practices to the use of available resources, thus extracting knowledge and information from oral traditions and local cultural values of indigenous peoples [93][94][95][96][97][98]. These practices are linked to certain mechanisms, such as flexible user rights and land tenure, adaptations for the generation, accumulation, and transmission of ecological knowledge, institutional dynamics, mechanisms for cultural internalization of traditional practices and associated worldviews and cultural values that contribute to both increased community solidarity, community engagement, and voluntary compliance, thus providing proper "rules" for marine and coastal ecosystem management [99,100].…”
mentioning
confidence: 99%
“…This is because their protection and development become the highest priority of indigenous communities [104]. The participation of local people is essential in planning and decision-making processes on issues related to the use and protection of the marine environment [94,96,99,105]. The exclusion of the local population from these processes jeopardizes the local community's trust, which is a prerequisite for efficient implementation [103].…”
mentioning
confidence: 99%